2016
DOI: 10.1016/j.psi.2016.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Evidence in promoting positive parenting through the Program-Guide to Develop Emotional Competences

Abstract: This study aims at providing evidence of the effectiveness of the Program-Guide to Develop Emotional Competences in promoting positive parenting. Contextual, institutional, methodological and professional issues were taken into account to develop a social innovation experience to support parenting as a preventive measure to family conflicts. The study describes both the contents of the Program-Guide and the methodological and evaluation issues that trained professionals need to consider when delivering the Pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
13

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 21 publications
1
15
0
13
Order By: Relevance
“…From the positive psychology perspective, in a community sample of adolescents, it was revealed that the most contributing factor to increase the subjective well-being is family self-concept (González-Carrasco et al, 2017). Finally, parenting studies analyzing the influence of parental practices on self-concept in Spain (Fuentes et al, 2015b; Riquelme et al, 2018), other European (Calafat et al, 2014) and Latin-American countries (Peru, Bustos et al, 2015; Carranza and Bermúdez-Jaimes, 2017; Brazil, Martínez et al, 2007; Martínez and García, 2008), and also in the United States (García et al, 2013), have shown that parenting characterized by the use of acceptance and involvement practices is associated with higher levels of self-concept, in several dimensions, than parenting characterized by the use of practices of strictness and imposition (Fuentes et al, 2011a,b; Martínez-González et al, 2016; Martínez et al, 2017, 2019). …”
Section: Introductionmentioning
confidence: 99%
“…From the positive psychology perspective, in a community sample of adolescents, it was revealed that the most contributing factor to increase the subjective well-being is family self-concept (González-Carrasco et al, 2017). Finally, parenting studies analyzing the influence of parental practices on self-concept in Spain (Fuentes et al, 2015b; Riquelme et al, 2018), other European (Calafat et al, 2014) and Latin-American countries (Peru, Bustos et al, 2015; Carranza and Bermúdez-Jaimes, 2017; Brazil, Martínez et al, 2007; Martínez and García, 2008), and also in the United States (García et al, 2013), have shown that parenting characterized by the use of acceptance and involvement practices is associated with higher levels of self-concept, in several dimensions, than parenting characterized by the use of practices of strictness and imposition (Fuentes et al, 2011a,b; Martínez-González et al, 2016; Martínez et al, 2017, 2019). …”
Section: Introductionmentioning
confidence: 99%
“…The decrease in psychosocial competence from early to late adolescence has been related to the increase in the influence of the peer group (Calafat et al, 2014;Dohnt & Tiggemann, 2006;Gardner & Steinberg, 2005;Smith, Chein & Steinberg, 2014;Veiga et al, 2015). Despite the increase in peer group influence, parental socialization continues to function as a fundamental source of protection from this psychosocial vulnerability (Baumrind, 1991;Calafat et al, 2014;Cerezo, Ruiz-Esteban, Lacasa & Gonzalo, 2018;Chan, Kelly, Carroll & Williams, 2017;García & Gracia, 2009;Martínez-González, Rodríguez-Ruiza, Álvarez-Blancoa, & Becedóniz-Vázquez, 2016). After numerous studies, there is still debate in the specialized literature about the best parenting strategy to preserve psychosocial competence throughout the adolescent period.…”
Section: Introductionmentioning
confidence: 99%
“…Given one of the main explanations of this result lies in the social role theory (Eagly & Wood, 2012), we suggest that, as one part of their overall approach, couples' therapist works on gender socialization processes to demystify gender stereotypes that may underlie human behaviour. Secondly, given the protective role that EI could play in conflict resolution as well as in psychological well-being and relationship's satisfaction, an effective form of treatment for such couples might be working on emotional competences (Martínez, Rodríguez, Álvarez, & Becedóniz, 2016). Specifically, we suggest that an EI training focused on the ability to perceive, regulate, and use the emotions of both partners during an conflict situation enable people how to connect with their partner, discuss their emotional experience, deal with them and, therefore, practice a new form of communication that should improve the couple dynamics (O'Connor et al, 2018).…”
Section: Discussionmentioning
confidence: 99%